FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI IKAN PADA NELAYAN KECIL (Studi di Desa Pecangaan Kabupaten Pati) - Herna Octivia Damayanti (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2018)
ENGLISHThe first fisheries management goal is to improve small fishermen’s quality of life. The small fishermen’s quality of life depends on the amount of income earned from the fishing activities. The purposes of this research are (1) to analyze the factors that influence the production of the fishermen in Pecangaan Village, (2) to calculate the return to scale of fishermen in Pecangaan Village. This research used descriptive quantitative method and was conducted on August 2016. The research location is in Pecangaan Village, Batangan Subdistrict. It mainly used primary data derived from the respondent (the fisherman in Pecangaan village). Secondary data were derived from the government of Pecangaan Village, Batangan Subdistrict. The number of processed data was 50 samples. The data analysis used Cobb-Douglas production function, in which dependent variable was production quantities and independent variable were: the amount of solar; the number of days at sea; the number of hours at sea; the sailing distance;fishermen’s consumption during the sailing, GT boats, number of crew and net’s width. The results of the research are (1) the significant factors are the number of days at sea; fishermen’s consumption during the sailing, GT boats and net’s width. Meanwhile, the insignificant factors are the amount of solar; the number of crew, the sailing distance and the number of hours at sea. (2) The value of return to scale in the production offisherman in Pecangaan Villageis -8.699, means it is in the condition of decreasing return to scale. INDONESIATujuan pengelolaan perikanan yang pertama yaitu untuk meningkatkan taraf hidup nelayan kecil. Taraf hidup nelayan kecil berhubungan dengan jumlah pendapatan yang diperoleh dari hasil tangkapan ikan yang didapat. Tujuan penelitian adalah (1) untuk menganalisis faktor-faktor yang mempengaruhi produksi nelayan Desa Pecangaan, (2) untuk menghitung skala hasil (return to scale) nelayan Desa Pecangaan. Penelitian ini menggunakan metode deskriptif kuantitatif dan dilaksanakan pada bulan Agustus 2016. Lokasi penelitian yaitu di Desa Pecangaan Kecamatan Batangan. Jenis data yang digunakan adalah data primer berasal dari responden (nelayan di Desa Pecangaan). Sedangkan data sekunder berasal dari Pemerintah Desa Pecangaan Kecamatan Batangan. Data yang diolah berjumlah 50 sampel. Analisis data dengan fungsi produksi Cobb-Douglas, dengan variabel terikat jumlah produksi dan variabel bebas adalah jumlah solar, jumlah hari melaut, lama trip, jarak melaut, konsumsi, GT kapal, jumlah ABK dan luas jaring. Hasil penelitian adalah (1) Faktor yang signifikan yaitu jumlah hari melaut, konsumsi, GT kapal dan luas jaring. Untuk faktor yang tidak signifikan adalah jumlah solar yang digunakan, jumlah ABK, jarak melaut dan lama melaut. (2) Nilai return to scale pada produksi nelayan Desa Pecangaan adalah -8,699 artinya dalam kondisi skala hasil yang menurun (decreasing return to scale).